PEMBERIAN PAKAN PELET YANG DICAMPUR PUPUK ORGANIK CAIR BIOTON TERHADAP PERTUMBUHAN IKAN NILA GIFT (Oreochromis sp) - Elrifadah Elrifadah; Deti Salawati (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
This study aims to determine the growth of tilapia gift fed pellets are mixed with a liquid organic fertilizer Bioton much as 10 cc / kg. Test fish are stocked as many as 20 tail  in nets hapa  measuring 1x1x1 m in the pond at  west Mandiangin village, Karang Intan of Banjar regency South Kalimantan for 42 days. During observations show that the results are quite good. the end result test fish weight of 271.5 g with initial weight of 69 g, weight relative growth of 293.48%, 1.109 feed conversion and feed efficiency rate of 90.196%. Waters conditions during the observation, the temperature range of 260-300C, and a pH range of 6.5-7.5. During maintenance avoid death or mortality of 0%, it shows the condition of maintenance medium used is quite supportive for the growth and survival of tilapia gift.